GAGASAN KREATIF BAMBANG SURYONO DALAM BEDAYA LAYAR CHENG HO - Nunik Widiasih (SURYA SENI, 2008)
Bedaya Layar Cheng Ho is a product of dance which to unify between the  essence of Bedaya dance from Surakarta style with China Beijing Opera. The bedaya takes theme of Cheng Ho sea voyage story. This bedaya is served in symbolic form with drama dance type, so that seen as the original product of the dance composer. The objective of this research of art study is to know the dance composer background, choreography and aesthetic of Bedaya Layar Cheng Ho, beside to make documentation and reference for the next art study. The research uses sociology, choreography and aesthetic approach. The background of the dance composer begins from Indonesia Karawitan High School (SMKI) which based on tradition of Surakarta style and then continues at Indonesia High School of Art (STSI) at Surakarta. His ability of the Java tradition increases after he gets dance skill from Gendhon Humardani, and active in Mangkunagaran palace as a dancer, choreographer, costume designer and also dance teacher. His concepts of tradition more develop after he joins withSardono’s dance theater.From the changes of Bambang Suryono his self, he has found personal expression on Bedaya Layar Cheng Ho. Bedaya Layar Cheng Ho uses Javanese dance media in form of bedayan, potehi puppet and Beijing opera. The bedayan seen as the uniﬁ cation between Hastha Sawanda and aesthetics of Beijing  opera, and shows the innovation and creative idea from the dance composer. This research also shows that tradition can be maintained with changes and development of their elements respectively. Keywords:  Bedaya Layar Cheng Ho, Aesthetics, and Creative Idea.